A comparative study of major clustering techniques for MAR learning usability prioritization processes - Lim K.C.; Selamat A.; Mohamed Zabil M.H.; Selamat M.H.; Alias R.A.; Mohamed F.; Krejcar O. (IOS Press BV, 2023)
Augmented reality; Hierarchical clustering; Usability engineering; Clustering techniques; Comparative studies; K-means; Mobile augmented reality; Mode-based; Prioritization process; Related works; Research methodologies; Iterative methods